Pengungkapan CSR pada Nilai Perusahaan dengan Profitabilitas dan Ukuran Perusahaan sebagai Variabel Moderasi - Narayana, I Putu Laksmana; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2021)
Firm value is a market-based value that can be observed in accounting through stock prices. One of the factors that influence firm value is Corporate Social Responsibility (CSR) disclosure. This study aimed to obtain empirical evidence regarding CSR disclosure on firm value by using the moderating variables of profitability and firm size to overcome the inconsistencies of previous studies. The theory used in this research is legitimacy theory and stakeholder theory. This research was conducted at SRI-KEHATI indexed companies on the Indonesia Stock Exchange for the 2017-2019 financial reporting year. The sampling technique used was the purposive sampling method; the number obtained was 75 observations. The analysis technique used is pure moderator regression analysis. The results showed that the higher the CSR disclosure, the higher the firm value, especially in companies with high profitability and large company sizes. Keywords: CSR Disclosure; Firm Value; Profitability; Firm Size.